Building Student Academic Achievement in the Post-Covid-19 Pandemic Era by Maximizing Student Satisfaction in Using the E-Learning Platform and Student Achievement Motivation - Novesar, Muhammad Refki; Yanuarmi, Dini; Putri, Geby Mareta (CV. Rayyan Dwi Bharata, 2024)
The inevitable development of technology also affects the world of education. Supported by the emergence of the Covid-19 Pandemic in early 2020. Demanding change in all aspects. No exception to the world of education. Where this causes changes to still achieve learning, namely by using LMS, which aims to make active learning accessible from anywhere. This causes changes in student motivation and satisfaction, in utilizing every facility in the world of education. This research aims to see whether the motivation of achievement and satisfaction of students who use LMS as learning in creating academic achievements owned by students. Using multiple regression analysis conducted on students studying on campus who use LMS in their learning. The results of this study obtained the results that each variable has a positive and significant influence on the academic achievement of students. Thus the utilization of LMS can increase the achievements of students, which gives rise to the power for educational institutions to increase the use of technology, especially LMS in learning.